Is a computer feeder necessary in the dry lot cow? - J.C. Kube; John E. Shirley; K.D. Frantz (Kansas Agricultural Experiment Station Research Reports, 1986)
Springing heifers and dry cows were introduced to a computer feeder either 2 wk before their estimated freshening date or at calving. There was no significant difference in milk production, percentage milk fat, percentage milk protein, or somatic cell count (SCC). Lead feeding with a computer feeder resulted in a 40% decrease in concentrate consumption over bunk feeding during the dry period.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Somatic cell count; Lactation; Feed cost